Dinâmica internação/desinternação em processos que resultaram em internação compulsória em hospital psiquiátrico - Pesente, Lucinéia (2009)
The citizenship of mental disorder (PTM) carriers has been claimed by a psychiatric reform movement. This reform pretends to question and also to extinguish the traditional psychiatric care model, which is self centered at the hospital institution. In this context a reduced hospitalization number triggers the use of a different strategy to supply this demand: hospitalization by the use of a law enforcement decision. In this particular case the hospitalization and discharging decisions are not entirely determined by the medical and care professionals but by a judicial decision. During the first semester of 2008 these ordered hospitalizations occupied, 11 of the 50 available berths for patients under crisis events, at the Short Permanence Unit (UCP) of Psychiatric Hospital (PH). Objecting to better understand this reality, this research analyses the prosecutions which resulted in hospitalizations and discharges at PH during 2008 first semester. The present work is a documental research with a qualitative approach and its sources were the judicial prosecutions that ended up in law enforced hospitalizations. Among the eleven identified cases, six could be analyzed by its prosecutions. The analyzed material were copied directly from the lawsuits or transcribed by the recorded readings performed during the constant visits to where they were stored. The data were analyzed by the content analysis proposed by Bardin(1997). The three principal axles of the analysis were developed over the hospitalizing/discharging dynamics: the family, the justice and the hospital. The main themes were distributed within these principal axles once they were interconnected. The data indicate that the time of enforced by law hospitalization 28 times greater than the non enforced. Beyond that, the responsible claimants of five hospitalizations had low incomes and lived under the pressure of other relatives who also required special care. The sixth case is of an individual who lived since childhood at institutions, and the last one of them were the claimer of the hospitalization. All the hospitalization claims allege PTM's agressivety. All the enforced claims initiated by an interdiction request, and all of them were attempted without a real investigation; the hospitalizations however presented custodial character. The hospital presents itself to be impotent against the law enforcements, ever since it can not deny them under the risk of the law penalties consequences; but also appears active in this process, constantly reporting to the justice about the conditions of the PTM's related to their discharges. We could notice that the hospitalization take different meanings to the evolved parts in its dynamics: to the family, it is a manner to be relieved from the overload they feel incapable to bare; for the justice, it seems to represent the prevention of a possible aggressive act, once there is already a history of danger; and for the hospital it is extreme measure that deviates its psycho stabilization basic purposes, furthermore it represents a throwback of the psychiatric reform principles.